2019
DOI: 10.20884/1.jap.2018.20.3.704
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Characteristics and Quality of Eggs from Laying Hens Fed on a Dried Papaya Peel Meal Diet

Abstract: The objectives of this study were to analyze the eggs nutritional characterics and quality from laying hens fed with diried papaya (Carica papaya L) peel meal diets. A total 200 brown laying hens strain MB 402 (42 week-old). The design used in this study was  a The objectives of this study were to analyze the eggs’ nutritional characteristics and quality from laying hens fed with dried papaya (Carica papaya L) peel meal diets. A total of 200 brown laying hens strain MB 402 (42 week-old) were used in this exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
2
1
0
Order By: Relevance
“…The improvement in yolk colour could be due to the presence of carotenoids such as β‐cryptoxanthin, lutein and β‐carotene in papaya pomace (Aroche et al., 2018); (AOAC, 2006). Similar to our findings, (Leke et al., 2018) reported that yolk colour intensity was significantly improved when papaya peel was fed to layers.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The improvement in yolk colour could be due to the presence of carotenoids such as β‐cryptoxanthin, lutein and β‐carotene in papaya pomace (Aroche et al., 2018); (AOAC, 2006). Similar to our findings, (Leke et al., 2018) reported that yolk colour intensity was significantly improved when papaya peel was fed to layers.…”
Section: Discussionsupporting
confidence: 93%
“…Serum biochemical parameters are the major indictors of metabolic alterations in tissue and organs reflecting diet effects on the nutrient metabolism and health of chickens (Bermudez and Stewart‐Brown, 2003). The reduction in serum total cholesterol and low density lipoprotein while high density lipoprotein was increased is in agreement with the results of (Leke et al., 2018) on papaya peels. The reduction of cholesterol in layers fed papaya pomace might be attributed to the presence of β‐sistosterol in papaya pomace which have hypoglycemic and hypolipidemic activity of impairing absorption of cholesterol in the small intestine ().…”
Section: Discussionsupporting
confidence: 92%
“…These results were within the standard range of egg yolk weight. Leke et al (2018) reported that the weights were 14.36 -15.52 g/egg. Tugiyanti et al (2012) in the study of the usage of fermented fish meal of up to 8% reported that average egg weight of layers: 54.03-58.33 g/egg, egg yolk weight: 12.31 -13.39 g/egg, eggshell weight: 6.26 -7.22 g/egg, egg index: 77.22 -89.66, hen day production: 41.67 -63.06 %, shell strength: 52.13 -59.13 mm, and HU: 70.41 -77.34 mm.…”
Section: Resultsmentioning
confidence: 99%